Immunohistochemical analysis of tumor-infiltrating lymphocytes in breast carcinoma: Relation to prognostic variables - Thanaa E. A. Helal; Eman A. A. Ibrahim; Amal I. A. Alloub (Wolters Kluwer Medknow Publications, 2013)
Background: The role of the tumor-infiltrating lymphocytes in invasive breast cancer and its correlation with different prognostic variables were always a matter of controversy in the literature. Aim: To determine the relative density of T lymphocytes, CD4+ cells, CD8+ cells, and B lymphocytes in breast cancer and assess their relationships with clinicopathologic parameters. Materials and Methods: Paraffin-embedded tissue sections from 48 invasive ductal carcinomas and 30 benign breast lesions were examined by means of immunohistochemistry to demonstrate CD3+, CD4+, CD8+, and CD20+. The immunophenotyped cells were semi-quantitatively graded into: Absent, intermediate, and extensive. Results: All lymphocyte populations were significantly more expressed in breast carcinomas than in benign lesions (P = 0.0001 for CD3+ and CD4+, P = 0.001 for CD8+, and P = 0.002 for CD20+ cells). In breast carcinoma, B and T cells were co-expressed in 33 of 48 tumors (68.8%). However, T cells were the predominant immunophenotype being noted in 81% of tumors, compared to B cells which were expressed in 50% of tumors. T cells, CD4+ and CD8+ cells were directly associated with patient's age (P = 0.004, P = 0.001, and P = 0.01, respectively). Clinical stages III and IV showed a significantly higher density of T and CD4+ lymphocytes than stage II (P = 0.004 and P = 0.009, respectively). Also, T and CD4+ cells were directly related to the histologic grade (P = 0.004 and P = 0.001, respectively). On the contrary, B lymphocytes were not related to any of the above-mentioned parameters. Conclusion: Although B and T lymphocytes were co-expressed in breast cancer, T lymphocytes and their subpopulations seem to have the upper hand in predicting the biological behavior. They probably promote neoplastic progression rather than acting as an antitumor immune response.